Seismic behaviour of shallow cut-and-cover tunnels - Zhengyao He; Nicolas G.L.H. Lee; S.P. Gopal Madabhushi (Soils and Foundations)
With increased demand for urban space, there is a growing propensity to move urban lifeline systems such as Metro systems and utilities to shallow, cut-and-cover tunnels. The seismic behaviour of such rectangular tunnels is important as these systems need to remain operational in the period after the earthquake for emergency rescue & recovery operations. In this paper, the main focus will be on determining the seismic response of shallow, rectangular tunnels that are buried in loose dry or saturated sand layers, and clay layers with different undrained shear strengths. The results from four centrifuge testing campaigns will be presented. The dynamic responses of the tunnel and soil will be compared to the input motion. The tunnel movements and soil deformations during seismic loading were obtained using high-resolution, high-speed imaging in combination with GeoPIV-RG software. Finally, conclusions will be drawn on the effects of the soil strata through which the tunnel passes, based on these centrifuge data that simulate the most critical geological conditions.